DAMPAK WISATA ISTANA KADRIAH TERHADAP SOSIAL DAN EKONOMI MASYARAKAT KELURAHAN DALAM BUGIS PONTIANAK TIMUR - Ihzar, Taupik; Asriati, Nuraini; Budiman, Jumardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the impact of the Istana Kadriah tourism object on the social and economic conditions of the community in Dalam Bugis Village, East Pontianak District. The research employs a qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that, from a social perspective, the local community continues to preserve their cultural values and traditional lifestyles despite frequent interactions with visitors from various regions and countries. Social interactions between residents and tourists are harmonious, polite, and friendly. Moreover, the community actively participates in managing the tourism area by serving as guards, guides, and volunteers in various cultural and religious activities, reflecting their sense of responsibility and concern for the preservation of local heritage. From an economic perspective, the existence of Istana Kadriah has created new income opportunities for residents through small businesses such as food, beverage, and souvenir sales. Traditional markets and microenterprises around the area have also grown in response to the increasing number of tourists. However, the management of Istana Kadriah still faces several challenges, including limited funding and inadequate facilities such as signage and waste disposal. Despite these constraints, the community’s spirit of independence and participation remains a key factor in maintaining the sustainability of this cultural tourism site. Overall, Istana Kadriah plays a significant role not only as a cultural tourism destination but also as a medium for social and economic empowerment within the local community